Gender Perceptions In Southeast Asian Countries : Findings From Jica-Ri Value Surveys - Yoshida, Kohei (Washington, DC: World Bank, 2012)
1. Introduction It is increasingly clear that gender equality varies conceptually from one country to another, as shown by indicators developed in the 1990s by several international organizations. The UNDP Human Development Report, for example, introduced two indicators in 1995: the Gender-related Development Index (GDI) and the Gender Empowerment Measure (GEM), both of which demonstrate that womens basic capabilities and the extent of their participation in political and economic decision-making processes are highly variable. While these and similar indicators are based on macro indices, some studies focus on the gender equality perceptions of individuals. The literature shows that attitudes toward gender equality are affected by respondents' own backgrounds, such as marital status and educational attainment, and that the effects can differ from one country to another. This research allows policy makers to differentiate groups and thereby to consider what kinds of policies can have what kinds of impacts on whose gender perceptions. The main difficulty with these types of studies is that they require large amounts of survey data on people's perception. Using data from a recently conducted value survey, the present paper looks at the gender perception of people in four Southeast Asian countries: Indonesia, Malaysia, Thailand, and the Philippines. The main objective is to determine which socio-demographic factors have significant impacts on people's attitudes toward gender issues in this historically and culturally diverse region. As is described in detail below, the analysis shows that Muslim identity tends to be associated with acceptance of male authority.